2009
DOI: 10.1038/jid.2008.319
|View full text |Cite
|
Sign up to set email alerts
|

Hotspot Mutation of Brahma in Non-Melanoma Skin Cancer

Abstract: Mammalian SWItch/sucrose non fermentable (SWI/SNF) remodeling of chromatin modulates transcription and DNA repair. The Brahma (BRM) catalytic subunit of the SWI/SNF complex is one of two mutually exclusive subunits that provide energy for remodeling. BRM has been identified as an important cancer susceptibility locus; however, to date no mutations have been identified in the BRM gene. We performed genetic analysis of BRM in human non-melanoma skin cancers, precancerous lesions, and normal skin revealing a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 19 publications
1
32
1
1
Order By: Relevance
“…65,66 A genetic analysis of BRM identified a common point mutation in 1 of 10 SCCs and in 2 of 6 basal cell carcinoma lesions that was absent from AKs and normal-appearing skin samples, suggesting that BRM is involved in disease progression. 67 A subsequent study reported that expression of BRM and BRG1 proteins was reduced approximately 10-fold in 100% of SCC (n = 11) and BCC (n = 5) specimens, but not in AK (n = 11) samples, which were similar to normal-appearing skin (n = 9). 68 These data suggest that loss of BRM and BRG1 expression is a late and necessary event in the progression of nonmelanoma skin cancer.…”
Section: Human Papillomavirusmentioning
confidence: 95%
“…65,66 A genetic analysis of BRM identified a common point mutation in 1 of 10 SCCs and in 2 of 6 basal cell carcinoma lesions that was absent from AKs and normal-appearing skin samples, suggesting that BRM is involved in disease progression. 67 A subsequent study reported that expression of BRM and BRG1 proteins was reduced approximately 10-fold in 100% of SCC (n = 11) and BCC (n = 5) specimens, but not in AK (n = 11) samples, which were similar to normal-appearing skin (n = 9). 68 These data suggest that loss of BRM and BRG1 expression is a late and necessary event in the progression of nonmelanoma skin cancer.…”
Section: Human Papillomavirusmentioning
confidence: 95%
“…In human cells the relevance of the BAF complexes to genomic stability is well illustrated by the findings that the mutually exclusive BRG1 (brahma-related gene 1) and BRM (brahma) ATPase catalytic subunits are tumor suppressor proteins [258,259]. Moreover, the ARID1A/BAF250 subunit, an E3 ubiquitin ligase that targets histone H2B [260], is mutated in $50% of ovarian clear cell carcinomas [261,262] and linked to other cancers [263][264][265].…”
Section: Baf Swi/snf Family Complexesmentioning
confidence: 99%
“…At least haploinsufficiency of BRG1 is recognized [25][26][27]62], while further studies are necessary whether such a role exists for STK11/LKB1 or not. Similar to BRG1, abnormalities of BRM in various cancers have been reported [58][59][60][61][63][64][65][66][67][68][69]. Though the early studies of cell lines and animal models strongly suggested subunits of SWI/SNF proteins as tumor suppressor, the first definitive evidence that members of these complexes function as tumor suppressive was shown by Versteege and colleagues.…”
Section: Roles Of Swi/snf Proteins In Cancermentioning
confidence: 95%